2021
DOI: 10.1002/hrdq.21431
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and followers' good and bad behaviors: A dual mediation model

Abstract: Drawing from social exchange theory and conservation of resources theory, the present study examines the effects of empowering leadership on followers' innovative work behavior (IWB) and organizational deviance through two underlying psychological mechanisms: (a) by developing followers' trust in leader and (b) by lowering followers' emotional exhaustion. The model was tested using a sample of 343 full-time Indian managerial employees who completed surveys at two time points separated by an approximate 2-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…Whereas empowerment is proven to be essential for organizational efficiency (Zhang et al, 2020), empowering leadership can reflect on a feeling of greater control over work (Liu et al, 2020;Zhang and Bartol, 2010) and reinforce responsibility towards individual and organizational results (Lee et al, 2018). In this study, empowering leadership is analyzed from a multidimensional perspective, which involves: highlighting the importance of work, encouraging participation in the decision-making process, expressing confidence in the high performance of employees and providing autonomy while facing bureaucratic limitations (Ahearne et al, 2005;Dash and Vohra, 2019;Rai and Kim, 2021;Singh and Rangnekar, 2020;Zhang and Bartol, 2010). Altogether these characteristics indicate how leaders empower their employees, as empowering leadership acts as a source of individual motivation and encourages autonomy and participation in decision-making (Sharma and Kirkman, 2015).…”
Section: Theoretical Background and Hypotheses Development 21 Effects...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas empowerment is proven to be essential for organizational efficiency (Zhang et al, 2020), empowering leadership can reflect on a feeling of greater control over work (Liu et al, 2020;Zhang and Bartol, 2010) and reinforce responsibility towards individual and organizational results (Lee et al, 2018). In this study, empowering leadership is analyzed from a multidimensional perspective, which involves: highlighting the importance of work, encouraging participation in the decision-making process, expressing confidence in the high performance of employees and providing autonomy while facing bureaucratic limitations (Ahearne et al, 2005;Dash and Vohra, 2019;Rai and Kim, 2021;Singh and Rangnekar, 2020;Zhang and Bartol, 2010). Altogether these characteristics indicate how leaders empower their employees, as empowering leadership acts as a source of individual motivation and encourages autonomy and participation in decision-making (Sharma and Kirkman, 2015).…”
Section: Theoretical Background and Hypotheses Development 21 Effects...mentioning
confidence: 99%
“…Seeing that empowering leadership has many prosocial effects (Shehawy, 2022), this study analyzes the contextual performance of employees, which exceeds the technical attributions of work and involves psychological and discretionary behaviors, such as: proactivity, interpersonal cooperation, persistence and organizational citizenship behaviors (Motowidlo and Van Scotter, 1994;Pradhan et al, 2018). Consistent with SET and its norms of reciprocity (Blau, 1964), these behaviors represent voluntary actions of the employees as a manner of supporting organizational goals (Shore et al, 2006), in exchange of feeling empowered by their leaders (Rai and Kim, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kwak and Jackson (2015) demonstrated that EL facilitates decision-making participation, in return providing subordinates with a greater sense of meaningfulness in their jobs. Some scholars argue that EL enhances subordinates’ confidence (Conger and Kanungo, 1988; Konczak et al , 2000), self-determination (Arnold et al , 2000; Konczak et al , 2000) and leaders to an impactful performance (Rai and Kim, 2021; Zhang and Bartol, 2010). In health care, Laschinger et al (2009) showed that structural changes in empowerment would lead to changes in PE, in return leading to improved job satisfaction.…”
Section: Hypothesesmentioning
confidence: 99%
“…Empowering leadership refers to the process whereby a leader grants power and responsibility to his or her subordinates by implementing a series of management actions, and it plays a dominant role in enhancing positive work outcomes among employees (Cheong et al , 2019; Sharma and Kirkman, 2015). However, some scholars have questioned whether the main effects of empowering leadership are positive, pointing out certain negative outcomes (Rai and Kim, 2021; Kim and Beehr, 2020a; Lorinkova and Perry, 2017; Wong and Giessner, 2018), non-linear effects (Lee et al , 2017; Sharma and Kirkman, 2015; Humborstad et al , 2014; Zhang et al , 2018) and paradoxical aspects inherent in its nature (Rai and Kim, 2021; Chen et al , 2011; Kim and Beehr, 2017, 2018). Even though such diverse effects of empowering leadership have been reviewed in previous works, the double-edged effect of empowering leadership highlighted here (a dual process with opposite effects on a focal work behaviour) has been largely overlooked (Cheong et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Empowering leadership promotes innovative behaviour among employees (Rai and Kim, 2021; Chen et al , 2011; Lim, 2021; Tang et al , 2020); specifically, the job resources made available and demands imposed by empowering leadership are crucial factors influencing employees’ innovative behaviours (Dediu et al , 2018; Messmann et al , 2017). Given the complexity and uncertainty of innovation, leaders cannot dictate the specific content or means of innovation; they can only encourage employees to take the initiative to solve problems by granting them sufficient power and responsibility in innovation-related work (Zhang and Bartol, 2010).…”
Section: Introductionmentioning
confidence: 99%